2021
DOI: 10.1007/s10854-021-05994-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ni2+ ions on the structural, morphological, photoluminescence, photo-catalytic and anti-bacterial studies of Cd0.9Zn0.1S nanostructures

Abstract: The present investigation reported the controlled synthesis of Cd 0.9 Zn 0.1 S and Cd 0.89 Zn 0.1 Ni 0.01 S nanostructures by simple chemical co-precipitation route. The XRD analysis confirmed the cubic structure of CdS on Zn doped CdS and Zn, Ni dual doped CdS without any secondary/impurity phases and no alteration in CdS cubic phase was noticed by Zn/Ni addition. The shrinkage of crystallite siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…For Zn-doped CdS, the value of the gap increases to 2.49 eV, and it is close to the value obtained by Zellagui et al for the same Cd 0.7 Zn 0.3 S alloys [63]. When adding the Ni to CdZnS material, the band gap decreases to 2.30 eV; the same behavior was observed by Raju et al [57]. They report a band gap reduction to 2.36 eV when a concentration of Ni equal to 1% is added into Cd 0.9 Zn 0.1 S alloys.…”
Section: Optical Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…For Zn-doped CdS, the value of the gap increases to 2.49 eV, and it is close to the value obtained by Zellagui et al for the same Cd 0.7 Zn 0.3 S alloys [63]. When adding the Ni to CdZnS material, the band gap decreases to 2.30 eV; the same behavior was observed by Raju et al [57]. They report a band gap reduction to 2.36 eV when a concentration of Ni equal to 1% is added into Cd 0.9 Zn 0.1 S alloys.…”
Section: Optical Analysissupporting
confidence: 90%
“…This result has been observed experimentally, as shown in section 3.4. A remarkable shift of the absorption through the higher wavelength region has been observed by P. Raju et al in their work [57]. They found that a nanostructure composition of Cd 0.89 Zn 0.1 Ni 0.01 S possesses a strong optical absorption for the lower wavelength, which enhances the optical absorbance in the visible wavelength, therefore showing that this nanostructure material improves the efficiency of optoelectronic devices.…”
Section: Optical Studymentioning
confidence: 62%
See 2 more Smart Citations